2019
DOI: 10.21873/anticanres.13976
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Vitamin D in Melanoma Development, Progression and Therapy

Abstract: Melanoma is one of the most lethal types of skin cancer, with a poor prognosis once the disease enters metastasis. The efficacy of currently available treatment schemes for advanced melanomas is low, expensive, and burdened by significant side-effects. Therefore, there is a need to develop new treatment options. Skin cells are able to activate vitamin D via classical and non-classical pathways. Vitamin D derivatives have anticancer properties which promote differentiation and inhibit proliferation. The role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 220 publications
(246 reference statements)
2
51
0
2
Order By: Relevance
“…One of them is the protection of VDR-defective human fibroblasts against DNA damage induced by UV mediated by the endoplasmic reticulum stress protein 57 (ERP57, MARRS) [18]. Therefore, the anticancer effects of vitamin D may be underlined by both genomic and non-genomic actions as UV-induced DNA damages, including cyclobutane dimers and (6-4)-photoproducts, are observed in skin cancers (reviewed in [19]).…”
Section: Vitamin D-an Essential Nutrient and A Potential Preventive Amentioning
confidence: 99%
“…One of them is the protection of VDR-defective human fibroblasts against DNA damage induced by UV mediated by the endoplasmic reticulum stress protein 57 (ERP57, MARRS) [18]. Therefore, the anticancer effects of vitamin D may be underlined by both genomic and non-genomic actions as UV-induced DNA damages, including cyclobutane dimers and (6-4)-photoproducts, are observed in skin cancers (reviewed in [19]).…”
Section: Vitamin D-an Essential Nutrient and A Potential Preventive Amentioning
confidence: 99%
“…Since vitamin D also exhibits antiproliferative and pro-differentiating properties, its deficiency has been correlated with the progression of several malignancies [ 70 , 215 , 216 , 217 , 218 , 219 ], especially breast [ 220 , 221 , 222 , 223 ], ovarian [ 224 , 225 ] and skin tumours [ 226 , 227 , 228 , 229 ].…”
Section: Vitamin D: State Of the Artmentioning
confidence: 99%
“…Previously, we found that changes in the expression of VDR, RORα, RORγ, CYP27B1 and CYP24A1 in melanomas correlate with melanoma progression and may affect the disease outcome . In addition, active melanogenesis stimulates the expression of HIF‐1α and HIF‐dependent pathways .…”
Section: Introductionmentioning
confidence: 96%